BACK ANALYSIS OF SIX-STOREY BUILDING’S PILE FOUNDATION BEARING CAPACITY FAILURE - Masyithah, Femy Sarah; Darjanto, Helmy (Jurnal Teknik Sipil, 2025)
This study investigated the foundation bearing capacity failure of a six-storey building, which was unsuccessfully mitigated by cement injection. Back analysis was carried out using soil investigation data (borehole logs, SPT values, and laboratory tests), static load tests (SLT), and pile driving analyzer (PDA) measurements to reassess the design of the pile group and the proposed piled-raft system. The axial capacity of the piles was evaluated with four commonly used methods—API, Revised Lambda, USACE, and FHWA—because they represent prevailing international and Indonesian practice and form the analytical basis for SNI 8460:2017. The analysis results revealed that the existing pile group was unable to withstand the applied working loads, and that the proposed piled raft did not satisfy the required design criteria. The back analysis further showed that, in very loose surface soils, the proportion of load carried by the raft should be limited to approximately 20% to avoid overstressing the soil and triggering additional settlement. This study contributes to a better understanding of the design and retrofit of piled-raft foundations in loose granular deposits by linking code-based capacity calculations with field load tests and by providing practical guidance for checking load sharing between piles and raft in soft ground conditions.